2012
DOI: 10.9790/2402-0224345
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of ‘OGI’ made from Malted Millet

Abstract: Abstract:The study aimed at investigating the quality of ogi made from malted millet. The fermented paste was made from millet at various levels (0, 5, 10%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Literature abounds with information on the production of ogi from maize (Bolaji, Adenuga-Ogunji, & Abegunde, 2017a;Okara & Lokoyi, 2012), millet (Inyang & Idoko, 2006;Olawale, Oyeleke, Akinro, & Olakunle, 2012), sorghum (Adelekan & Oyewole, 2010;Apotiola, 2013), or the combination of two or more of these cereals (Eke-Ejiofor, 2018; Odewole et al, 2017). However, despite being one of the most important cereal crops in the world, as well as the most economically important crop in developing countries (Ajala & Gana, 2015), there is dearth of information on the suitability of rice for ogi production.…”
Section: Introductionmentioning
confidence: 99%
“…Literature abounds with information on the production of ogi from maize (Bolaji, Adenuga-Ogunji, & Abegunde, 2017a;Okara & Lokoyi, 2012), millet (Inyang & Idoko, 2006;Olawale, Oyeleke, Akinro, & Olakunle, 2012), sorghum (Adelekan & Oyewole, 2010;Apotiola, 2013), or the combination of two or more of these cereals (Eke-Ejiofor, 2018; Odewole et al, 2017). However, despite being one of the most important cereal crops in the world, as well as the most economically important crop in developing countries (Ajala & Gana, 2015), there is dearth of information on the suitability of rice for ogi production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, the Bureau of Agricultural Statistics (BAS) reported that the rice production in the Philippines significantly increased from 15.77 million metric tons in 2010 to 16.68 million metric tons in 2011 and 18.03 million metric tons in 2012 [3]. With this, the accumulated millions of tons of waste rice hull generated annually poses a substantial problem for rice growers with regards to its disposal [1,4,5]. Rice hull (RH) contains 13-29 wt% inorganic compounds of which 87-97 wt% is silica and the RH composition depends on the rice variety, climate, geographic location, soil, and quantity of fertilizer used [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…With this, the accumulated millions of tons of waste rice hull generated annually poses a substantial problem for rice growers with regards to its disposal [1,4,5]. Rice hull (RH) contains 13-29 wt% inorganic compounds of which 87-97 wt% is silica and the RH composition depends on the rice variety, climate, geographic location, soil, and quantity of fertilizer used [4,[6][7][8]. Hence, waste rice hull can be a good source of silica and its utilization can circumvent disposal problem and can be an alternative renewable source of this compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it would be a big waste of noble raw material to throw it away, since it can be used in various industries such as electronics, construction, ceramics, chemical industry, manufacture of photovoltaic cells, among others [6]. A large number of uses for this waste have been reported in literature by authors such as [13,17,14,27,12,1,5,11]. Moreover, clay is composed of colloidal particles of diameter less than 0.005 mm, with high plasticity when moist, and when dried, forms lumps hard to dissociate by finger pressure [15].…”
Section: Introductionmentioning
confidence: 99%